Tiller population dynamics in eight cultivars of elephant grass during undisturbed growth - Rueda Barrientos, José Ángel; Ortega-Jiménez, Eusebio; Enríquez-Quiroz, Javier F.; Palacios Torres, Rogelio Enrique; Ramírez Ordoñes, Sergio (Taylor & Francis, 2018)
The aim of the study was to assess tiller population dynamics of aerial and basal tillers in eight cultivars of Pennisetum purpureum (Schumach.), syn. Cenchrus purpureus (Schumach.) Morrone, in a warm humid climate in Veracruz, Mexico. This is a pioneer study on tiller population dynamics in elephant grass under conditions of undisturbed growth. The tiller population assays included data from 14 days after cutting until 154 and 182 days after cutting for the dry and wet seasons, respectively. On each sampling date, a distinctive ring was placed on every new tiller, and rings were removed from dead tillers. Tiller density, mortality and appearance were determined. In wet seasons, copious tillering occurred on initial regrowth (by day 42, mostly aerial tillers, with a ratio of 2:1 to 4:1 for aerial to basal tiller appearance), and on day 98 (a higher proportion of basal tillers, with an aerial to basal tiller ratio of 1.5:1). Aerial tillers showed a higher overall mortality rate than basal tillers (29.0 vs 14.4). Younger basal tillers showed higher mortality than older tillers. Higher tiller density occurred during the dry season, where it increased gradually until day 70 and then declined. The cultivars ‘Cameroon‘, ‘CT115‘ and ‘OM22‘ showed remarkably high tillering ability. The findings indicate that harvesting a forage bank is possible from day 70 during a dry season.
Keywords: Dinámica de densidad; Hierba rey; Tasa de aparición de macollos; Tasa de mortalidad de los cultivadores; Pastos tropicales